Assessment of neutralizing capacity of antibodies raised in mice against a Crotalus durissus terrificus phosphodiesterase - Alonso, Maria del Rosario (2019)
Phosphodiesterases (PDE) belong to a super-family of enzymes that have multiple roles in the metabolism of nucleotides. These enzyme classes have played such a critical role as tools in the field of molecular biology, but their function is little known today. Here, we evaluated the humoral response induced by a PDE from Crotalus durissus terrificus (CDT) venom used as antigen. The PDE of the Crotalus durissus terrificus venom (CDT-PDE) was purified by gel filtration chromatography (Sephadex G-75) and ion exchange chromatography (HiTrap Q-FF). The CDT-PDE activity was tested by chromogenic reaction with sodium salt of bis (p-nitrophenyl) phosphate and the purity was monitored by SDS-PAGE. BALB /c mice (n= 5) were immunized subcutaneously with 0.3, 0.6 and1.2 µg of enzyme (CDT-PDE) on days 1, 15 and 30, respectively. Freund's complete adjuvant was used in the first immunization and incomplete adjuvant in the booster. On day 50, mice were sacrificed and plasma antibody titers were evaluated by ELISA and cross-reactions with Bothrops alternatus and B. diporus venoms were analyzed by dot blotting. Mice plasma showed a specific response to CDT-PDE and antibodies gave titers around 1/1600. About of dot blotting test, C.d.t venom and it’s PDE showed strong spots were noted in each case, but partial and negative reactions were noted on B. diporus and B. alternatus, respectively. The neutralization capacity of PDE- antibodies was 40 and 20 % when different amounts of serum were analyzed (36.66 µl; 18.33 µl). These results demonstrated that CDT-PDE produces a humoral response. PDE-CDT antibodies recognize the crotalic PDE and, to a lesser extent, the PDE present in the venom of B. diporus. These antibodies can be used as tools in the study of the effect of PDE on platelet aggregation, as well as in the purification of PDE by affinity chromatography to improve the performance in the isolation from CDT venom.